Application of Time Domain Index and Kurtosis analysis Method in the Fault Diagnosis of Rolling Bearing - Guo Qingfeng; Wang Chengdong; Liu Peisen (Jixie chuandong)
The application of time domain index and kurtosis analysis method in the fault diagnosis of rolling bearing is studied. Firstly,the kurtosis values of each signals are obtained by equi- spaced and different frequency band- pass filter of bearing signals. Secondly,through the maximum principle of kurtosis value,the frequency band of the fault diagnosis is determined,and then the frequency range is determined as the filter parameters. Finally,by calculating the time domain index of filter to diagnose the rolling bearing. The test results show that the frequency band range obtained through this way is reasonable,which will also improve the rate of diagnosis accuracy.